Efecto de la desinfección con agua electroactivada sobre la calidad de tomates - Denoya, Gabriela Inés; Soteras, Trinidad; Pesquero, Natalia; Maitia, Carolina Soledad; Leiton, Héctor Rafael; Cristos, Diego Sebastian (Instituto de Fisiología Vegetal, CONICET-UNLP, 2024)
Poster